Implementasi Metode Cluster Analysis K-Means dalam Segmentasi - Engelberth Worabai; Alva Hendi Muhammad; Tony Hidayat (Jurnal Ilmiah Komputasi, 2023)
UMKM smilax ointment is a business that sells goods in the form of ointments that are useful for the male reproductive organs. These MSMEs still use traditional business strategies and use computer technology only for database creation. Smilax ointment UMKM product is Smilax cream which consists of 3 packages, namely 100 grams, 80 grams, and 40 grams. The research was conducted using the UMKM database and the clustering method used was k-means clustering because K-means is non-hierarchical in accordance with the data obtained from UMKM. In addition, k-means is able to classify data very quickly compared to fuzzy k- means[1]. This research includes the stages of data collection, preprocessing, analysis process (k-means), evaluation, and conclusions. The results of the clustering classification which was carried out four times based on the type of packaging, obtained a value of k = 2 where the cluster "0" is the unproductive region/city and cluster "1" is the most productive region/city, namely Jakarta and Jayapura both for the 100 gram, 80 gram, packaging type. and 40grams.